The Use of Endorsement in Online Media Marketing Strategy - Virginia Mandasari; Daisy Marthina Rosyanti (Future Science, 2023)
Recently, many people have been using Instagram. Instagram is social media that allows users to share photos. Instagram can be used as a marketing communication through sharing photos of products that will sell. Instagram allows consumers to view photos of products and can directly comment below the photo of the desired product. This research aimed to determine how Instagram was chosen as a medium of marketing communication. This research used a qualitative approach to obtain in-depth results and seven strategies to rigorous the methods. This research chose Instagram because Instagram become one of the social media that growing rapidly. After the coding process, there founded four keywords: the reason Instagram was chosen, Instagram benefits, the use of endorsement, and disadvantage endorsement. This research found that endorsement on Instagram has three components that are subject to attribute endorsement: trustworthiness, respect, and similarity.